Enhancing Academic Writing Through Critical Thinking Learning Logs among Indonesian EFL University Students - Ratu Anisa Kafur; Astri Rahma Wati; Olivia Anava; Dwi Oktaviani; Indri Lestari; Nuryansyah Adijaya (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Integrating critical thinking (CT) into English as a Foreign Language (EFL) writing instruction presents ongoing challenges, particularly in non-Western academic settings such as Indonesia. Therefore, this study investigates using CT-oriented learning logs to improve academic writing performance among EFL university students at STKIP PGRI Lampung. The research aimed to enhance students’ ability to develop coherent arguments and express reasoned perspectives in writing. Employing a mixed-methods design, the study involved 35 second-semester students who participated in a 14-week intervention that combined opinion writing, summary tasks, and reflective responses. Quantitative data were collected through pre- and post-tests assessed using holistic and analytical rubrics, while qualitative data were derived from thematic analysis of students’ reflective logs. Results indicated significant improvements in writing fluency, argumentative structure, and quality of reasoning. However, aspects such as the clarity of topic sentences and paragraph cohesion remained areas for development. The findings contribute to the growing literature on CT in EFL contexts and demonstrate that structured reflective practices can effectively support the development of academic writing. This study offers practical implications for EFL educators aiming to integrate critical thinking into writing pedagogy through accessible and contextualized strategies.